NEBIVOLOL ROLE IN THE CORRECTION OF INTRACARDIAC HEMODYNAMICS IN PATIENTS WITH CHRONIC HEART FAILURE - R. L. Dzhanaeva; Z. T. Astakhova; V. Yu. Makoeva (Российский кардиологический журнал)
Aim. To assess the effectiveness and safety of a super-selective vasodilating β-adrenoblocker (β-AB) nebivolol in patients with NYHA Functional Class (FC) I–III chronic heart failure (CHF), as a complication of coronary heart disease (CHD). Material and methods. In total, 42 patients with post-infarction cardiosclerosis and FC I–III CHF (30 men and 12 women), aged 52–73 years, were examined. Nebivolol was administered once daily, in the morning, as a part of complex CHD treatment, for 12 weeks. The clinical effectiveness of the therapy and its effects on intracardiac hemodynamics (echocardiography) were assessed. Results. After 12 weeks of the treatment, clinical manifestations of CHF decompensation (oedema, dyspnoea, palpitation, and fatigue) were reduced, the mean CHF FC significantly decreased from 3,12±0,08 to 1,88±0,05 (p<0,05), and exercise capacity increased. A significant reduction in systolic and diastolic blood pressure levels was observed among hypertensive patients. In all participants, mean heart rate was significantly reduced, from 76,80±10,41 to 62,0±5,54 bpm (p≤0,05). Nebivolol also improved the parameters of pathological cardiac remodelling and intracardiac hemodynamics. Mean end-diastolic and end-systolic volume decreased by 19,5% and 15,7%, respectively, while mean left ventricular (LV) myocardial mass decreased by 22,4%. Improved systolic function manifested in significantly increased LV ejection fraction (by 23,8%) and fractional shortening (by 38,3%). Nebivolol also improved LV diastolic function, as demonstrated by increased Ve and F/A ratio (from 1,12±0,34 to 1,29±0,45; p<0,05). Conclusion. Nebivolol therapy improved clinical status and extra- and intracardiac hemodynamics in patients with CHF.